Neoliberalism, Governance, & Capital Accumulation: A Study of Development Debates and Social Dynamics in Indonesia - Airlangga, Sinergy Aditya (Magister Ilmu Administrasi Publik, 2024)
Governance is a concept for the development of good government management. On the one hand, this concept seems to be a new breakthrough in providing public services and regional development. On the other hand, the concept of governance is said to be a concept that drives the neoliberal agenda for market development. The impact of this often causes environmental damage, social conflict and inequality. This article aims to portray the government development debate and social dynamics occurring in Indonesia. Theoretically, this article shows the debate about understanding the concept of governance and the various views that accompany it. Empirically, instead of the governance view being said to encourage improvements in public services with social development, it actually encourages market access for the benefit of capital accumulation in Indonesia. This article seeks to answer three basic questions. First, how does neoliberalism shape the concept of governance; Second, how does the concept of governance encourage capital accumulation; and Third, how development debates shape social dynamics in Indonesia. This paper uses a desk study by collecting several secondary manuscripts and tends to focus closely on theoretical debates. In the end, this article wants to conclude an argument that governance practices are closely related to the neoliberalism agenda which actually encourages opening up market access and wider capital flows. Such conditions will become a new problem in the development of community welfare.